Project developer options to enhance the value of solar electricity as solar and storage penetrations increase. (15th December 2021) - Kim, James Hyungkwan; Mills, Andrew D.; Wiser, Ryan; Bolinger, Mark; Gorman, Will; Crespo Montañes, Cristina; O'Shaughnessy, Eric
Highlights: Photovoltaic (PV) project developers have a range of configuration options. Analyze more than ten strategies to preserve the marginal grid value of PV. Limited impact of shifting the timing of PV generation at the expense of total generation. Shifting the timing of generation becomes redundant when storage is added. At high penetrations, leading options add storage to configurations that maximize PV generation. Abstract: Increasing the penetration of photovoltaics (PV) reduces the marginal grid value of PV electricity. The declining grid value of PV with higher penetration could limit the technology's economic attractiveness and future demand. Various strategies have been proposed for preserving this value. Using a consistent framework, we analyze the net value (accounting for both cost and grid value) of more than ten strategies in the United States. Here, grid value is estimated from coincident wholesale power market prices and PV generation using observed historical prices or modeled future prices with up to 30% PV penetration. We find that established and emerging strategies designed to shift the timing of standalone PV generation at the expense of total generation—including orienting monofacial PV modules west or bifacial modules vertically—result in minor net-value benefits or penalties. Adding energy storage to such systems magnifies the net-value loss, because configurations that change the timing of PV production become redundant when the energy-shifting capabilities of storage are added. The largest net-value gains come from strategies that maximize generation (solar tracking plus oversized PV arrays) in conjunction with storage, especially at high PV penetrations. PV systems are long-lived assets. Our results suggest that efforts to promote generation-maximizing strategies today may yield increasing net-value benefits as PV and storage deployments continue to accelerate in the United States over the coming decades.